Effects of multiple disturbance processes on arboreal vertebrates in eastern Australia: implications for management. Issue 4 (11th November 2013) - Anson, Jennifer R.; Dickman, Chris R.; Handasyde, Kath; Jessop, Tim S.
<x xml:space="preserve">Abstract</x> Habitat loss and invasive predators increasingly threaten global biodiversity. Here we use a landscape‐scale experimental approach to explore the individual and synergistic effects of logging and an invasive predator, the red fox Vulpes vulpes on two common native arboreal vertebrates (a predator and prey species) in south‐eastern Australia. We used site occupancy methods to evaluate different models evaluating the effects of site specific forest logging disturbance, lethal fox baiting and forest structural elements for explaining variation in site occupancy of a large monitor lizard Varanus varius, and a marsupial prey, the common ringtail possum Pseudocheirus peregrinus across a complex forest landscape. Site occupancy of ringtail possum was influenced by habitat resources and the structural complexity of forest, which indirectly mediated predation risk. Presence of fox baiting had no direct effect on the ringtail site occupancy. In contrast, access to prey resources and fox baiting appeared to best explain site occupancy variation in monitor lizards across the landscape. While these species are affected primarily by separate disturbances, synergistic interactions between the processes may intensify their effects. Our results demonstrate that species susceptibility to disturbance processes are highly idiosyncratic. This approach makes efficient use of integrated modelling to aid conservation management at both local and landscape levels.